Analisa Metode El Chinix Traduisant La Realite (Electre) dan Weighted Product (WP) Untuk Pendukung Keputusan Perekrutan Karyawan - Sitorus, Anggiat Selamat; Sihombing, Volvo; Munthe, Ibnu Rasyid (MEANS (Media Informasi Analisa dan Sistem), 2021)
Human resource management (HR) is important to achieve company goals. One of the activities in HR management is recruitment, selection, and training. Recruitment and selection are usually carried out without using a system so that the calculations are still done manually. However, by processing data using the system, it can produce a decision in recommending prospective employees who can have a positive impact on the company. The company selection process is carried out in two stages, namely official selection and final selection in the form of psychological tests, interviews, ability tests, and communication. The use of the Elimination Et Choix Traduisant La Realite (ELECTRE) method at the official selection stage and the Weighted Product (WP) method at the final selection stage is a discovery made to obtain the best decision according to the required criteria. By using this method, the final result will be obtained, namely recommendations from several prospective employees who are fit to work in the company. The results of this system performance reached one hundred percent; the data from the system is in accordance with the expected calculations.